PREVENTION AND TREATMENT OF INTRAABDOMINAL HYPERTENSION IN PATIENTS WITH PATHOLOGY OF ABDOMINAL ORGANS - A. Kolosovych (Ukrainian Scientific Medical Youth Journal, 2016)
Encreased intra-abdominal pressure attracts the attention of scintistslast years. Abdominal compartment syndrome cause the development of acute distress syndrome and multiple organ failure in 40% with a fatal outcome of the disease in 12% of cases. Unfortunately, there is no explicit algorithm of actions to prevent the development of abdominal syndrome in the literature. That’s why so importent to search for new technical solutions for the prevention and treatment of intra¬abdominal hypertension in patients with acute surgical pathology of abdominal organs.